2006
DOI: 10.1161/circulationaha.105.597526
|View full text |Cite
|
Sign up to set email alerts
|

The Chemokine and Chemokine Receptor Profile of Infiltrating Cells in the Wall of Arteries With Cardiac Allograft Vasculopathy Is Indicative of a Memory T–Helper 1 Response

Abstract: Background-Despite improvement in short-term patient survival after heart transplantation (HTx), long-term survival rates have not improved much, mainly because of cardiac allograft vasculopathy (CAV). Cytokines and chemokines are considered to play an important role in CAV development. Interleukin-4 and interleukin-10 were expressed at the same level in both HTx groups and references. In HTxϩCAV, all CϩCR, but especially the T-helper 1 (TH1) CϩCR, were more abundant than in the HTxϪCAV and references. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(91 citation statements)
references
References 33 publications
3
88
0
Order By: Relevance
“…van Loosdregt et al found that the expression of IFN-␥, IFN-␥-inducible chemokines (Mig, IP-10, ITAC, RANTES, and fractalkine/CX3CL1), and markers of IFN-␥-secreting T H 1 cells (CXCR3, CCR5, and CX3CR1) were increased in epicardial coronary arteries from transplanted hearts with documented GA compared with referent specimens. 27 The activation of T H 1 responses was specific for GA as the expression of the T H 2 cytokine IL-4 and the T H 3 cytokine IL-10 were similar to that of arteries from transplanted hearts without GA or nontransplanted hearts. Further analysis of the specimens revealed that IFN-␥ and T H 1-associated chemokine receptors and their ligands were expressed in the intima and adventitia but not in the media, which had a 5-fold lesser leukocytic infiltrate.…”
Section: Evidence For a Pathogenetic Role Of Ifn-␥ In Gamentioning
confidence: 89%
See 2 more Smart Citations
“…van Loosdregt et al found that the expression of IFN-␥, IFN-␥-inducible chemokines (Mig, IP-10, ITAC, RANTES, and fractalkine/CX3CL1), and markers of IFN-␥-secreting T H 1 cells (CXCR3, CCR5, and CX3CR1) were increased in epicardial coronary arteries from transplanted hearts with documented GA compared with referent specimens. 27 The activation of T H 1 responses was specific for GA as the expression of the T H 2 cytokine IL-4 and the T H 3 cytokine IL-10 were similar to that of arteries from transplanted hearts without GA or nontransplanted hearts. Further analysis of the specimens revealed that IFN-␥ and T H 1-associated chemokine receptors and their ligands were expressed in the intima and adventitia but not in the media, which had a 5-fold lesser leukocytic infiltrate.…”
Section: Evidence For a Pathogenetic Role Of Ifn-␥ In Gamentioning
confidence: 89%
“…90 Additionally, IFN-␥ induces the expression of chemokines in human ECs, such as CXCR3, CCR5, and CX3CR1 ligands, that have a role in T H 1 cell activation and recruitment. 27,38 As mentioned above, despite a similar expression of IFN-␥-inducible proinflammatory molecules, human VSMCs do not activate T cells and can inhibit T-cell responses to ECs. 49 One explanation is that IFN-␥ induces a far greater expression of the enzyme indoleamine 2,3-dioxygenase in VSMCs than in ECs and the depletion of tryptophan in the microenvironment by indoleamine 2,3-dioxygenase leads to inhibition of T-cell activation and proliferation (M.C.C.…”
Section: Effects Of Ifn-␥ On Vessel Wall Cellsmentioning
confidence: 95%
See 1 more Smart Citation
“…1,4,17) The animal models of CAV were reported from rodents to large animals. The distinctive differences between rodents and swine are immune systems and cardiovascular systems.…”
Section: Discussionmentioning
confidence: 99%
“…Damage to the endothelium leads to smooth muscle cell proliferation, infiltration of the intima with inflammatory cells, and collagen deposition. 22 This process causes the evolution from focal intimal thickening early after transplant to circumferential diffuse thickening and development of atherosclerotic plaques at later stages. 23,24 The absolute amount of intimal hyperplasia tends to be constant in the entire arterial tree but is more noticeable in the distal vasculature given the smaller lumen size 25 ( Figures 1 and 2).…”
mentioning
confidence: 99%